Bias in emerging biomarkers for bipolar disorder. Issue 11 (19th May 2016) - Carvalho, A. F.; Köhler, C. A.; Fernandes, B. S.; Quevedo, J.; Miskowiak, K. W.; Brunoni, A. R.; Machado-Vieira, R.; Maes, M.; Vieta, E.; Berk, M.
Abstract : Background: To date no comprehensive evaluation has appraised the likelihood of bias or the strength of the evidence of peripheral biomarkers for bipolar disorder (BD). Here we performed an umbrella review of meta-analyses of peripheral non-genetic biomarkers for BD. Method: The Pubmed/Medline, EMBASE and PsycInfo electronic databases were searched up to May 2015. Two independent authors conducted searches, examined references for eligibility, and extracted data. Meta-analyses in any language examining peripheral non-genetic biomarkers in participants with BD (across different mood states) compared to unaffected controls were included. Results: Six references, which examined 13 biomarkers across 20 meta-analyses (5474 BD cases and 4823 healthy controls) met inclusion criteria. Evidence for excess of significance bias (i.e. bias favoring publication of 'positive' nominally significant results) was observed in 11 meta-analyses. Heterogeneity was high for ( I 2 ⩾ 50%) 16 meta-analyses. Only two biomarkers met criteria for suggestive evidence namely the soluble IL-2 receptor and morning cortisol. The median power of included studies, using the effect size of the largest dataset as the plausible true effect size of each meta-analysis, was 15.3%. Conclusions: Our findings suggest that there is an excess of statistically significant results in the literature of peripheral biomarkers for BD. Selective publication of 'positive' results and selective reporting of outcomes are possible mechanisms.